Mechanistic study of the hsa_circ_0074158 binding EIF4A3 impairing sepsis-induced endothelial barrier - Liao, Haiyan; Li, Yiming; Zhang, Li; Peng, Zhiyong; Zhang, Zhaohui (Frontiers in Immunology, 2025)
BackgroundSepsis remains a major clinical challenge, characterized by high rates of morbidity, mortality, and healthcare burden. Its complex pathogenesis involves multiple factors, with damage to the vascular endothelial barrier being a key component. Currently, there are no widely accepted biomarkers that demonstrate high sensitivity and specificity for sepsis, and treatment mainly focuses on supportive care without specific therapeutic targets. Recent research suggests that circRNA has potential as both a biomarker and a therapeutic target. In previous studies, the harmful role of hsa_circ_0074158 in worsening sepsis-induced endothelial barrier dysfunction was demonstrated through both in vitro and in vivo models, highlighting its potential as a biomarker and therapeutic target for sepsis.MethodsThis study examined how hsa_circ_0074158 affects endothelial barrier function in sepsis. The role of hsa_circ_0074158 (circ_Ctnna1 in mice) in sepsis-related endothelial barrier dysfunction was studied using both in vitro and in vivo models. RNA pull-down, RNA immunoprecipitation (RIP), and actinomycin D experiments were used to show that circ_0074158 impacts endothelial barrier function in sepsis by reducing the stability of the host gene CTNNA1 (mRNA) after binding to EIF4A3.ResultsIn both LPS-treated human umbilical vein endothelial cells (HUVECs) and cecal ligation and puncture (CLP) murine models, the overexpression of hsa_circ_0074158 (the mouse homolog of hsa_circ_0074158 is named circ_Ctnna1) significantly decreased CTNNA1 mRNA stability and increased endothelial hyperpermeability, while its knockdown restored barrier integrity. Mechanistically, RNA pull-down and RNA RIP assays demonstrated that hsa_circ_0074158 directly binds to the RNA-binding protein (RBP) EIF4A3, which decreases the stability of CTNNA1 (mRNA) and the production of α-catenin, subsequently impairing endothelial barrier function in sepsis. Rescue experiments showed that dual targeting of hsa_circ_0074158 and EIF4A3 restored endothelial barrier function. The dysregulation of the hsa_circ_0074158/EIF4A3 axis exacerbates sepsis-induced endothelial barrier dysfunction by destabilizing CTNNA1 mRNA, posing a critical medical challenge due to its complex pathophysiology.ConclusionsThis study provides new insights into the molecular mechanisms of sepsis and suggests potential therapeutic targets for its treatment. Further research is needed to explore the clinical application of these findings.